Animal behaviour and cancer. (March 2015) - Vittecoq, M.; Ducasse, H.; Arnal, A.; Møller, A.P.; Ujvari, B.; Jacqueline, C.B.; Tissot, T.; Missé, D.; Bernex, F.; Pirot, N.; Lemberger, K.; Abadie, J.; et al.
Abstract : Scientists are increasingly coming to realize that oncogenic phenomena are both frequent and detrimental for animals, and must therefore be taken into account when studying the biology of wildlife species and ecosystem functioning. Here, we argue that several behaviours that are routine in an individual's life can be associated with cancer risks, or conversely prevent/cure malignancies and/or alleviate their detrimental consequences for fitness. Although such behaviours are theoretically expected to be targets for natural selection, little attention has been devoted to explore how they influence animal behaviour. This essay provides a summary of these issues as well as an overview of the possibilities offered by this research topic, including possible applications for cancer prevention and treatments in humans. Highlights: Oncogenic phenomena are observed in nearly the entire animal kingdom. They are both frequent and detrimental for animals. Behaviours may evolve due to the selection associated with oncogenic processes. The study of those behaviours deserves to receive more attention. This research area may lead to applications for cancer prevention and treatments.